Peer-reviewed and unbiased research, rather than 'sound science', should be used to evaluate endocrine-disrupting chemicals. Issue 11 (13th July 2016) - Trasande, Leonardo; Vandenberg, Laura N; Bourguignon, Jean-Pierre; Myers, John Peterson; Slama, Remy; vom Saal, Frederick; Zoeller, Robert Thomas
Abstract : Evidence increasingly confirms that synthetic chemicals disrupt the endocrine system and contribute to disease and disability across the lifespan. Despite a United Nations Environment Programme/WHO report affirmed by over 100 countries at the Fourth International Conference on Chemicals Management, 'manufactured doubt' continues to be cast as a cloud over rigorous, peer-reviewed and independently funded scientific data. This study describes the sources of doubt and their social costs, and suggested courses of action by policymakers to prevent disease and disability. The problem is largely based on the available data, which are all too limited. Rigorous testing programmes should not simply focus on oestrogen, androgen and thyroid. Tests should have proper statistical power. 'Good laboratory practice' (GLP) hardly represents a proper or even gold standard for laboratory studies of endocrine disruption. Studies should be evaluated with regard to the contamination of negative controls, responsiveness to positive controls and dissection techniques. Flaws in many GLP studies have been identified, yet regulatory agencies rely on these flawed studies. Peer-reviewed and unbiased research, rather than 'sound science', should be used to evaluate endocrine-disrupting chemicals.